Level Depresi pada Pasien Gagal Ginjal Kronis yang Sedang Menjalani Dialisis - Septa Meriana Lumbantoruan; Lisandra Maria Goretti Bernadette Sidabutar (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to identify depression and depression-related variables from demographic and disease-related data in chronic kidney failure (CKD) patients undergoing dialysis. The method used in this study was a cross-sectional descriptive approach by conducting short interviews to fill in the provided form containing 20 statements. The results showed that almost 20% of the respondents indicated that they had symptoms of depression. In conclusion, it is known that antihypertensive drugs are associated with depression, whereas patients who do not receive antihypertensive drugs have a higher depression score. In line with that, comprehensive treatment and early assessment of the mental status of CRF patients are critical to overcoming the physical and psychological burden of the medicine being undertaken. Keywords: Depression, Dialysis, Chronic Renal Failure, Kidney